1989
DOI: 10.1002/hep.1840090314
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between oxygen transport and oxygen uptake in patients with cirrhosis: Effects of vasoactive drugs

Abstract: To elucidate the relationship between oxygen transport and uptake in cirrhosis, we studied the effects of three vasoactive drugs that change O2 transport. Systemic hemodynamics, blood gases and lactate concentration were measured in patients with alcoholic cirrhosis before and after intravenous dobutamine, propranolol and nitroglycerin. Nine patients received successively dobutamine and then propranolol. Ten patients received nitroglycerin. Three other patients without cirrhosis (controls) received dobutamine.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

1991
1991
2001
2001

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…To date, Moreau et al 25 are the only investigators to systematically study whole-body oxygenation in patients with CESLD. They found that the administration of dobutamine to patients with cirrhosis resulted in significant increases in both DO 2 and VO 2 without significant changes in the a-vO 2 difference or oxygen extraction ratio.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, Moreau et al 25 are the only investigators to systematically study whole-body oxygenation in patients with CESLD. They found that the administration of dobutamine to patients with cirrhosis resulted in significant increases in both DO 2 and VO 2 without significant changes in the a-vO 2 difference or oxygen extraction ratio.…”
Section: Discussionmentioning
confidence: 99%
“…The present study evaluated essentially the same parameters as Moreau et al, 25 with two major modifications to the study design. First, VO 2 was measured independently of DO 2 to avoid mathematical coupling, 26 which can occur because of the presence of shared variables in the equations for calculating both DO 2 and VO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Oxygen and carbon dioxide tensions and pH were measured at 37°C with speci®c electrodes 9 while oxyhaemoglobin saturation was measured using the spectrophotometric method (2500 CO-Oxymeter, Corning Medical, Med®eld, MA). 9 …”
Section: Measurements Of O 2 -Derived Variables and Acid-base Statusmentioning
confidence: 99%
“…Since somatostatin has a portal hypotensive action, 6±8 this substance may enhance the decrease in portal pressure due to b-blockade. On the other hand, since both b-blockers 9,10 and somatostatin 8 decrease cardiac index, a combination of these substances may result in a marked decrease in this variable, making the administration of somatostatin hazardous in b-blocked patients. Thus, more information is needed on the haemodynamic effects of a combination of somatostatin and a non-selective b-blocker.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation